The Influence of Card Media on Adolescent Women's Knowledge and Attitudes About Stunting : A Pre-Experimental Study at State Senior High Schools 2, Central Buton, Sulawesi Southeast Sulawesi in 2024 - Tri Eka Andryani (Universitas Ibn Khaldun Bogor, 2026)
Stunting is still a health problem in Indonesia. Central Buton Regency was once ranked first with the highest prevalence of stunting rate at 41.6%. One of the targets for accelerating stunting reduction is adolescents. Adolescents tend to be more interested in interactive delivery methods accompanied by tools or media that involve all the senses. The use of card media can be done by adding game elements that help display the material more easily and also establish interaction between teachers and respondents, and also make it easier for the goal to absorb the information provided. The purpose of this study is to determine the influence of card media on the knowledge and attitudes of adolescent girls about stunting at state senior high school 2 Central Buton, Southeast Sulawesi. This study is a quantitative research with a Pre-Experiment research method using a One Group Pre-test and Post-test design. The research population is 60 students in grade XII of state senior high school 2 Central Buton with sampling using a total sampling technique so that a sample of 60 people was obtained. The instrument is in the form of a questionnaire to measure the knowledge and attitudes of adolescent girls about stunting using research materials in the form of card media containing information about stunting. The average results of the knowledge score of adolescent girls about stunting before being given a pretest intervention had less knowledge (5.4) and after the posttest became good (8.2). Meanwhile, the average attitude of pretest (22) and posttest (35). The results of the T-test showed a p value of 0.001 for the effect of card game education on knowledge and 0.001 for the effect of card games on attitude. The results <0.05 which indicates the influence of card media on the knowledge and attitudes of adolescent girls of state senior high school 2 Central Buton, based on this study it is suggested that students can apply stunting prevention in adolescent girls, the school can use the game as a teaching reference, can socialize the game to those who have not been exposed and for the next researcher can develop the game in terms of regulations so that it can be better understood and effective.